(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study determined National Directorate of Employment Basic National Open Apprenticeship Scheme trainees’ ratings of their employability in Anambra State. Two research questions and two null hypotheses guided the study. The descriptive survey design was adopted. All the population, which was 240 NDE B-NOAS 2021 trainees from three Local Governments in Anambra State, was used as the sample. A 63-item questionnaire was used for data collection, which were validated by three experts. Test re-test reliability method was employed, and Pearson Product Moment Correlation Co-efficient was used to determine the reliability of the instrument, which yielded an overall co-efficient of 0.87. Mean and standard deviation were used to answer the research questions, while analysis of variance (ANOVA) was used to test the hypothesis. The findings revealed that NDE B-NOAS trainees possessed high technical and ICT skills after their training for employability in Anambra State. There was a significant difference in the mean ratings of graduates of tertiary institutions and school leavers of lower level of education on their technical skills and ICT skills for employability after NDE B-NOAS training in Anambra State. It was, therefore, concluded that that adoption of technical skills and ICT skills will go a long way to increase the quality of manpower and reduce the rate unemployment or dependence on government for job. Based on the findings, it was recommended among others, that effective instructional technique and strategies should be adopted by trainers to achieve employability skills necessary for the world of work for their trainees.